Estudio del comportamiento de hormigones hidráulicos, a partir del empleo de áridos reciclados sin y con adiciones de materiales finos - Peralta González, Yadira; Clavero Rodríguez, Armando (Universidad Central "Marta Abreu" de las Villas, 2014)
The purpose of this investigation is the study of the behavior of hydraulic concretes, starting from the employment of recycled arid with and without additions of fine materials. For this, the recycled material was obtained by means of the trituration of premixed concrete (this material come from the concrete factory Chiqui Gómez located in Santa Clara, Cuba). It was carried out a study of the physical and mechanical properties of the recycled material, for its employment in the elaboration of concretes, with 100% of natural arid, a combination of 25% of the coarse fraction with 50% of the fine fraction, both fractions recycled, and 100% of arid recycled, adding in the three cases 3% and 6% finer material that the sieve 100. The physical and mechanic behavior of the concrete elaborated to the age of 7 days was analyzed, concluding that for a bigger percent of substitution the resistance to compression diminishes. It was also obtained, for a 100% of natural arid mix and the mentioned combination, that as the fine percent smaller than sieve 100 increases (up to 10%) the resistance is increased. With the employment of these recycled materials a sustainable alternative is looked to give solution to current problems of exhaustion of raw mix natural product of the exploitation of quarries, contributing in a positive way to the economic and social development of the country. .
Keywords: Comportamiento de Hormigones Hidráulicos; Áridos Reciclados; Materiales Finos; Fábrica de Hormigón Chiqui Gómez Ubicada en Santa Clara, Cuba; Behavior; Materials